2020
DOI: 10.1002/app.49643
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of surface aminolysis and hydrolysis on improving fibroblast cell colonization within poly(L‐lactide) scaffolds

Abstract: This work presents a method for overcoming the low internal cell colonization within the tissue engineering scaffolds. 3D scaffolds were fabricated by the compression molding/salt leaching technique from mixtures of aminolyzed and hydrolyzed poly(L-lactide) single crystals (PLLAsc) with poly(D,L-lactide) (PDLLA) microparticles. Modified PLLAsc were used to guarantee the surface hydrophilicity, while PDLLA microparticles were used to reinforce the scaffolds. Mechanical properties, morphology, water uptake and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…1 Scaffolds, drug delivery systems, and implants are modied in different ways depending on the form and chemistry of the material and application site. In the case of polymer scaffolds commonly used methods are plasma treatment, 2,3 wet chemistry (hydrolysis, aminolysis), 4 layer by layer technique, 5 surface gra polymerization, 6 coating with inorganic particles 7,8 and biomolecule immobilization. 9,10 Most frequently, these modications concern changing wettability, surface energy, topography, or surface elasticity or introducing charged groups or bioactive motives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Scaffolds, drug delivery systems, and implants are modied in different ways depending on the form and chemistry of the material and application site. In the case of polymer scaffolds commonly used methods are plasma treatment, 2,3 wet chemistry (hydrolysis, aminolysis), 4 layer by layer technique, 5 surface gra polymerization, 6 coating with inorganic particles 7,8 and biomolecule immobilization. 9,10 Most frequently, these modications concern changing wettability, surface energy, topography, or surface elasticity or introducing charged groups or bioactive motives.…”
Section: Introductionmentioning
confidence: 99%
“…Aminolysis can be exploited as a single-step approach to enhance cell response as a result of improved wettability and/or presence of positive charge. 4,6,26 On the other hand, the aminolysis technique is frequently used as an intermediate step before further physical or chemical immobilization of biomacromolecules. 27,28 There are also other approaches to introduce free amine groups on the material surface.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly promising results were achieved by using cell-laden hydrogel-based strategies, as cells are directly embedded in a 3D microenvironment that allows for their mobility and self-organization to replicate the developmental processes that lead to the organs development. In cell-seeded scaffold approaches, on the contrary, cells are seeded on (macro)porous scaffolds that, despite potentially promoting tissue ingrowth after in vivo implantation, require particular efforts in the design of pores, porosity and interconnectivity to allow for full scaffold colonization, which remains challenging [ 217 ], and subsequent cell self-organization. Finally, most of the described approaches require manually prepared cell-laden scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the electrochemical performance of MnO 2 , we synthesize Co 3 O 4 @MnO 2 @PPy composite electrode by using the Co 3 O 4 nanowire and PPy as the core and shell, respectively. Through testing, we found that the "core-shell-shell" structure makes use of synergistic effect [39][40][41][42] to obviously promote the process of charge transfer, obtain higher capacitance, and improve the material's multiplier ability and cycling stability. In addition, the application of electrodeposition to protect the PPy coating is conducive to stabilizing the SEI membrane and protecting the structural collapse of manganese dioxide during the long cycle.…”
Section: Introductionmentioning
confidence: 99%